Les migrantes de retour dans la Corne de l’Afrique - Amina Saïd Chiré; Bezunesh Tamru (EchoGéo)
The growing demand for maids in the Republic of Djibouti and in the Middle East countries encourage female migration from Ethiopia and from Somalia. During their stays abroad, migrant women will have several strategies in order to return successfully back home. Our study thus questions the ways these return are implemented in term of resettlements and socio-spatial reintegration in Ethiopia. Indeed, the study shows that a "return" to be a final and rewarding "stay" must undergo countless international trips followed by several domestic mobilities. These returns and "final staying’s" are more frequent in urban areas, the Ethiopian case shows also that secondary towns and the suburbs of the capital city are areas mostly preferred by returnees. Beyond these facts, the findings of the study unveil the way female returnees readdress the question of urban changes by their social as well as by their gender specificities.